FRAMING LANDSCAPE: FILM AND GEOGRAPHIC EXPERIENCES OF THE PLACE - Costa, Maria Helena Braga e Vaz; Rycroft, Simon (Sociedade e Território, 2025)
Within cultural geography, film, place, and landscape are representational practices sharing a similar dimension of living and experiencing the world. Accordingly, films, with their panoramic landscape’s imagery and the camera’s various points of views on the specificities of places, landscapes, and events, give places a distinctive meaning. Therefore, the objective of this article is to discuss the ways in which Pernambuco filmmakers make their films unique in terms of a new way of imagining the landscape and place working between the regionalist and non-regionalist imaginary. So, this article explores the constrasting poetic experience of the Brazilian northeast semi-arid landscape and place in films such as Cinema, Aspirins and Vultures (Cinema, Aspirinas e Urubus, Marcelo Gomes, 2005) and Arid Movie (Árido Movie, Lírio Ferreira, 2006).